Synthesis of Alkyd Resin Modified with Waste Palm Cooking Oil as Precursor Using Pretreatment with Zeolite Adsorbent - Fitrilia Silvianti; Wijayanti Wijayanti; Wisnu A.A. Sudjarwo; Wikan Berliana Dewi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2018)
Research on synthesis of alkyd resin (AR) modified with waste palm cooking oil (WPCO) as precursor using alcoholys-polyesterification method was successfully conducted. The modified alkyd resin was characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Thermogravimetry-Differential Thermal Analysis (TG-DTA). The pretreatment was carried out for WPCO by applying adsorption technique using zeolites to remove free fatty acid (FFA). Modified alkyd resin was synthesized with the main ingredients composition consisting of WPCO, glycerol, anhydrous phthalate with the oil length of 40% at the total weight of 27.54 grams, and a small amount of CaO as catalyst. The characterization result using FTIR showed the presence of typical alkyd resin compound group at the absorption peaks 1597.06 and 1651.07 consecutively as the vibration of benzene ring from the phthalate and C=C stretching of unsaturated fatty acids. The thermal characterization was performed by using TG-DTA analysis showing that the transition glass and recrystallization at the temperature 390.25 °C and 482.46 °C respectively.